1998
DOI: 10.1111/j.1349-7006.1998.tb00586.x
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Hyperthermia for Cancer Using Magnetite Cationic Liposomes: An in vivo Study

Abstract: The effect of hyperthermia on solid glioma tissue formed subcutaneously in the left femoral region of female F344 rats was investigated. Magnetite cationic liposomes (MCLs), which have a positive surface charge, were used as heating mediators for intracellular hyperthermia. MCLs were injected into the solid tumors, which were then subjected to irradiation by an alternating magnetic field (118 kHz, 384 Oe). The rats were divided into four groups, which received no irradiation (control: group I), or irradiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 208 publications
(33 citation statements)
references
References 19 publications
1
31
0
1
Order By: Relevance
“…Recently, a number of in vivo studies using animal models were undertaken where MNPs were injected into a tumor followed by AMF exposure and resulting changes in the tissue and organs were investigated. These include C3H mouse mammary carcinoma [63] , mouse EL4 T-lymphoma [11] , MX11 mouse sarcoma [64] , human prostate cancerous and bone marrow cells in transgenic mice [46] , EL4 mouse T-lymphoma [65] , T-9 rat glioma cells [66] , B16 mouse melanoma [67] , MM46 mammary and skin carcinoma [68] , murine B16-F10 mouse melanoma [69] , cat mammary tumor gland [70] , Os515 hamster osteosarcoma [71] , VX-7 squamous cell carcinoma in rabbit tongue [72] , DMBA induced rat mammary carcinoma [73] , and human glioma cells. [74] Most of the studies though provided positive evidence for decrease in tumor size due to hyperthermia, there is a clear lack of complete information on host and material response.…”
Section: 0 Magnetic Nanomaterials For Hyperthermia-based Therapymentioning
confidence: 99%
“…Recently, a number of in vivo studies using animal models were undertaken where MNPs were injected into a tumor followed by AMF exposure and resulting changes in the tissue and organs were investigated. These include C3H mouse mammary carcinoma [63] , mouse EL4 T-lymphoma [11] , MX11 mouse sarcoma [64] , human prostate cancerous and bone marrow cells in transgenic mice [46] , EL4 mouse T-lymphoma [65] , T-9 rat glioma cells [66] , B16 mouse melanoma [67] , MM46 mammary and skin carcinoma [68] , murine B16-F10 mouse melanoma [69] , cat mammary tumor gland [70] , Os515 hamster osteosarcoma [71] , VX-7 squamous cell carcinoma in rabbit tongue [72] , DMBA induced rat mammary carcinoma [73] , and human glioma cells. [74] Most of the studies though provided positive evidence for decrease in tumor size due to hyperthermia, there is a clear lack of complete information on host and material response.…”
Section: 0 Magnetic Nanomaterials For Hyperthermia-based Therapymentioning
confidence: 99%
“…A subcutaneous fibre optic thermometer was used for intratumoural temperature measurements. In a later study, the same group subcutaneously implanted T-9 rat glioma cells into the femoral region of rats followed 11 days later by intratumoural injection of MCLs using an infusion pump [101]. The first MHT session was performed 24-h after the MNP infusion for 30 min.…”
Section: Magnetic Hyperthermia Therapymentioning
confidence: 99%
“…[8b] Later, Yanase et al (1998) showed similar results using magnetic cationic liposomes, observing regression of most tumors. [16] In another contribution, Yanase et al (1998) observed evidence of an antitumor immune response when tumors were treated with hyperthermia. [17] Subcutaneous tumors grown on both femurs of a rat disappeared completely after only a single side was treated.…”
Section: Hyperthermia – the Current Paradigm In Thermal Cancer Thementioning
confidence: 99%